Management and Outcomes of Open Abdomen: A Review of the Literature and Two Case Reports from Central Uganda - Wismayer, Richard (New Horizons in Medicine and Medical Research Vol. 3, 2022)
A laparostomy is defined as the intentional separation of the musculofascial and cutaneous layers of the abdominal wall. Open abdomen is a procedure used among surgeons to reduce the effects of life-threatening insults that may lead to intra-abdominal hypertension and eventually abdominal compartment syndrome. In East Africa, despite the high incidence of conditions requiring open abdomen there are few reports documenting its use and outcomes. The author reports on two patients which were managed with an open abdomen in central Uganda. One patient was operated for a perforated peptic ulcer and another had an anastomotic leak. In both cases, a Bagota bag was used for temporary abdominal closure. In this case series fascial closure was eventually achieved and no mortality was reported. The aim was to provide a review of the literature on the different techniques used for temporary abdominal closure and the management of these critically ill surgical patients. In Africa only 25% of patients who survived underwent fascial closure, whilst the mortality of laparostomy in Africa is as high as 44%. This may be due to the severity of the underlying pathology rather than the technique used for temporary abdominal closure. In East Africa, further research is needed to understand the indications and optimal treatment strategies for open abdomen to reduce the morbidity and mortality of these surgical critically ill patients.